The impact of macroeconomic variables towards economic growth : Evidence from 10 developing countries / Siti Nor Assyurah Sapilih - Sapilih, Siti Nor Assyurah (2018)
One of the most of important targets for any developing country is to achieve high economic growth. There are many factors that affect economic growth and this paper concern on the impact of macroeconomic variables towards economic growth by using the evidence from 10 Developing Countries. The macroeconomic variables that used for this study are unemployment rate, inflation rate, tax revenue and trade. The main objective for this study is to examine the impact of macroeconomic variables towards economic growth. This study using three panel unit root test which are LLC, Breitung and IPS and Robust Standard Error as a correction model. The function of Panel Unit Root Test is to investigate the relationship between the macroeconomic variables and economic growth. Result of the panel unit root test indicates that only GDP and INF that significant at level while UNEMP, TAX and TRADE significant at First Order Different. After conducting Panel unit root test, the BPLM and Hausman Test must be conducted to identify whether this study is pooled by using OLS or pooled by Random Effect and Fixed Effect. This study pooled by Random Effect and proceeds with Robust Standard Error due to the existence of Heteroskedasticity. After conducting Robust Standard Error, the variable that has significant relationship with economic growth is unemployment rate and trade. Hence, this study concludes that only unemployment rate and trade has significant relationship towards economic growth.